Elastic constants and internal friction of forged β-solidifying TiAl alloys at room temperature and high temperature. (March 2022) - Adachi, K.; Waki, H.
Abstract: Forged β-solidifying TiAl alloys can exhibit nine independent elastic constants in accordance with the orthorhombic symmetry of forging texture. In this study, we measured the elastic constants and high-frequency internal friction of two forged Ti–43Al–5V–4Nb (in at.%) alloys with nearly lamellar and triplex microstructures using resonant ultrasound spectroscopy at temperatures between room temperature and 760 °C. We demonstrated that a two-step heat treatment after the forging process produces nearly isotropic elasticity in the TiAl alloys, and the elastic anisotropy is virtually constant with temperature. The Young's modulus of the TiAl alloy with a triplex microstructure was comparable to that of the alloy with a nearly lamellar microstructure. In addition, the triplex-microstructure TiAl alloy showed a significant energy loss for shear vibration modes compared with the nearly lamellar alloy. These findings are supported by the effect of the hexagonal ω-phase present in the βo -phase on mechanical stiffness and loss. Internal friction measurements at high frequencies exhibited an internal-friction peak at approximately 200 °C, which may be related to the isothermal ω-phase. This research may contribute to the development of sophisticated forged TiAl components. Highlights: Two-step heat treatment after hot forging produced nearly isotropic elasticity. ω-phase is an important factor affecting mechanical stiffness and loss. Anomalous stiffening near 500 °C was observed. Internal-friction peak at approximately 200 °C was observed.